2019
DOI: 10.1038/s41419-019-1752-5
|View full text |Cite
|
Sign up to set email alerts
|

mTOR hyperactivation in Down Syndrome underlies deficits in autophagy induction, autophagosome formation, and mitophagy

Abstract: Down syndrome (DS), a complex genetic disorder caused by chromosome 21 trisomy, is associated with mitochondrial dysfunction leading to the accumulation of damaged mitochondria. Here we report that mitophagy, a form of selective autophagy activated to clear damaged mitochondria is deficient in primary human fibroblasts derived from individuals with DS leading to accumulation of damaged mitochondria with consequent increases in oxidative stress. We identified two molecular bases for this mitophagy deficiency: P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 70 publications
3
95
1
Order By: Relevance
“…Consistent with these findings, PINK1 and Parkin-dependent mitophagy is impaired and mTOR is hyperactivated in primary human fibroblasts derived from individuals with Down syndrome. In this context, inhibition of mTOR using AZD8055 restores autophagic flux, as well as mitophagy initiated by PINK1 and Parkin (Bordi et al, 2019).…”
Section: The Role Of Mitophagy In Agingmentioning
confidence: 99%
“…Consistent with these findings, PINK1 and Parkin-dependent mitophagy is impaired and mTOR is hyperactivated in primary human fibroblasts derived from individuals with Down syndrome. In this context, inhibition of mTOR using AZD8055 restores autophagic flux, as well as mitophagy initiated by PINK1 and Parkin (Bordi et al, 2019).…”
Section: The Role Of Mitophagy In Agingmentioning
confidence: 99%
“…Studies with CCCP and FCCP in a non-mitophagy context, have reported that these proton uncouplers cause a reduction in mTORC1 activity, suggesting that PINK1/Parkin mitophagy might require mTOR inactivation as bulk autophagy does (Inoki et al, 2003;Kim et al, 2013;Bartolome et al, 2017). Furthermore, recent reports suggest that mTORC1 hyperactivation can have an inhibitory effect on PINK1/Parkin mediated mitophagy as well as general autophagy (Bartolome et al, 2014(Bartolome et al, , 2017Bordi et al, 2019). Importantly, hypoxia leads to a reduction in mTORC1 activity as well, meaning that mTORC1 might play a role in hypoxiainduced mitophagy (Vadysirisack and Ellisen, 2012).…”
Section: Does Mtorc1 Regulate Mitophagy?mentioning
confidence: 99%
“…The role of mTORC1 as regulator of both general autophagy and mitophagy induction after oxidative phosphorylation uncoupling is well established (Bartolome et al, 2017). Accordingly, pharmacological inhibition of mTOR using AZD8055, which inhibits both mTORC1 and mTORC2 (Chresta et al, 2010), restored autophagy and mitophagy in DS fibroblasts (Bordi et al, 2019). As mentioned before, we previously demonstrated hyperactivation of mTOR in the Ts1Cje hippocampus (Troca-Marín et al, 2011).…”
Section: Discussionmentioning
confidence: 60%
“…In fact, altered mitochondrial function has long been associated with DS (reviewed by Valenti et al, 2014;Izzo et al, 2018). It has been recently found damaged mitochondria linked to increased oxidative stress, reduced mitophagy and reduced autophagy, together with mTOR hyperactivation in fibroblasts from DS patients, (Bordi et al, 2019). The role of mTORC1 as regulator of both general autophagy and mitophagy induction after oxidative phosphorylation uncoupling is well established (Bartolome et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation